The cultural changes among Kelantan community before and after flood disaster in Kelantan - Daud, Lutfi; Utaberta, Nangkula; Othuman Mydin, Md Azree (WARIS Research Group, UPM, 2017)
Flood is a natural phenomenon. However, flood disaster is able to cause bad physical and mental damages. For instance, 2014 flood disaster in Kelantan has given a huge effect for Kelantan people. This research will study about culture comparison of Kelantan community between before and after the flood disaster. In order to conduct the research, a qualitative method research which involves content analysis is the most suitable approach. At the end of this research of cultural study, it isbelieved to be able to show the differences of culture between before and after flood 2014. This is important in order to understand the effect of disaster upon culture of a community, which directly able to increase the preparedness of that particular community to face the upcoming disaster again